2022
DOI: 10.3126/ijosh.v12i2.39022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinal extension exercises on mechanical low back pain in work from home IT professionals in India

Abstract: Introduction: Prolonged sitting with awkward posture and long working hours are the predisposing factors for developing Mechanical Low Back Pain (LBP) in IT professionals. Poor dynamic trunk extension performance is associated with back-related permanent work disability and recurrence of LBP. The purpose of this study was to find and analyze the effect of spinal Extension exercises on Mechanical Low Back Pain in work from home IT professionals. Methods: In this comparative study, 50 work from home IT professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The effect of intervening with the corset of these muscles might give better outcomes. Recent research findings highlight the promising results for back pain like the effect of hydrotherapy-based exercises,[ 21 ] activity-specific spinal stabilization exercises,[ 13 ] and movement control spinal exercise are becoming better options for chronic nonspecific LBP. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of intervening with the corset of these muscles might give better outcomes. Recent research findings highlight the promising results for back pain like the effect of hydrotherapy-based exercises,[ 21 ] activity-specific spinal stabilization exercises,[ 13 ] and movement control spinal exercise are becoming better options for chronic nonspecific LBP. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The strength is graded on the ability of the patient to keep the low back flat on the surface and the angle at which the back arches are noted and correlated with Kendall’s MMT grading system. [ 13 ] Kendall’s Upper Abdominal Strength Test: It is used to evaluate upper abdominal strength. The grade is assigned according to Kendall’s MMT grading system.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…International Labour Organization [ 12 ] survey mentions that the COVID-19 pandemic has severely affected workplace dynamics, where around 68% of the world's total workforce, and 81% of employers had to close down their workplaces [ 12 ]. In contrast, during the pandemic, Tata Consultancy Services (TCS) reported that 85% of its employees (40,00,000 in India and outside India) shifted to WFH within a short time and its performance remain unchanged, which was reflected in its higher stock prices [ 13 ]. Variance in WFH practices has effects on individuals, families, and organizations and the possibility of state views on tax and labour laws.…”
Section: Introductionmentioning
confidence: 99%